Mortalidad atribuida a diabetes mellitus registrada en el Ministerio de Salud de Perú, 2005-2014 - Atamari-Anahui, Noe (2018)
Objective. To estimate the mortality attributable to diabetes mellitus (DM) as recorded by Peru’s Ministry of Health and its association with the human development index (HDI). Methods. This was an ecological study based on a secondary analysis of death records belonging to the Ministry of Health for the period from 2005 to 2014. A death was considered attributable to DM if the underlying cause of death given in the death record was DM. Mortality attributable to DM has been presented descriptively and in terms of geospatial analyses, and Spearman’s rho was used to test for an association between the difference in the mortality attributable to DM (between 2005-2006 and 2013-2014) and the HDI in Peru’s various departments.